Algunas vicisitudes del régimen societario colombiano derivadas de la interpretación constitucional - Reyes Villamizar, Francisco (2023)
Corporate law in Colombia ha s experienced difficulties recen tly because of the way in which the Constitutional Court has led the pr ocess of constitutionalization of private law, thereby affecting legal stability in a way that is inconvenient to the proper functioning of the national legal system. Two elements especially affect the stability and certainty of the system: first, the lack of meticulousness of many opinions of the Constitutional Court, and, second, the legislative branch’s slow response in light of its duty to counteract judicial pr ecedents that affect the basic investment conditions in a market economy. This article analyzes more than ten rulings of the Constitutional Court, arranging them in two time periods, and in them the aforementioned lack of meticulousness is evident: for example, it is very difficult to determine what the rationale of the opinion is, and a deficient use of the doctrine of stare decisis is clearly made, in which the binding force of previous opinions is not even upheld.